Inovasi Teknologi Smart Pelletizer Ramah Lingkungan untuk Produksi Pakan Ikan Efisien dan Berkelanjutan bagi Warga Bulupitu - Widiyanti; Riana Nurmalasari; Muhammad Idris Effendi (Al-DYAS, 2026)
The high cost of commercial feed, which accounts for 60–70% of total operating costs, is a major constraint for fish farmers in Bulupitu Village, Gondanglegi Subdistrict, Malang Regency. This condition has prompted some farmers to use food waste as an alternative feed, despite its low nutritional content and its tendency to accelerate the deterioration of pond water quality. This community service program aims to implement an appropriate technological innovation in the form of a smart pelletizer to improve the efficiency of fish feed production using local raw materials. This technology integrates mixing with a capacity of 20 kg per batch, molding, and drying in a heating chamber to produce floating pellets. The implementation results show that the use of the smart pelletizer increased feed production capacity and rate compared with conventional methods and reduced the partner’s feed costs by 40–50%, from Rp12,000–Rp14,000/kg for commercial feed to Rp6,500–Rp7,500/kg. The application of this technology contributes to improving the efficiency of fish farming enterprises through the use of local raw materials and reduced dependence on commercial feed. The sustainability of the program requires the implementation of stock storage methods to anticipate fluctuations in raw material availability and regular assistance with laboratory testing to maintain the consistency of the feed’s nutritional content.